The Role of Innate and Adaptive Immune Responses in The Pathogenesis of Periodontitis: A Narrative Review - Yunita, Rahma; Oktariana, Desi (Sriwijaya Journal of Medicine, 2025)
Periodontitis is a complex disease that attacks periodontal tissue by progressive damage caused by various factors lead to inflammatory process. The progression of periodontitis is associated with bacterial activity that induces an inflammatory response in the host. Changes in the composition of bacteria within dental plaque leading to increased inflammation of the periodontal tissue which triggers the activation of inflammatory mediators from the host. Relative studies were identified and collected through case report and review article in Medline/Pubmed, Sciencedirect, Wiley Online Library and Google Scholar websites from 2011 until 2024. In addition to producing a chronic inflammatory process, periodontitis induces immune system dysregulation, which leads to microbial dysbiosis in the subgingival and submarginal locations. Both the humoral and cellular components of the innate and adaptive immune systems are plays crucial role for periodontitis. Periodontitis is a chronic disease and an advanced stage of gingivitis, when the immune system fails to counter bacterial invasion, the inflammatory process persists, and leading to extensive damage to periodontal tissues.